Isolation, identification, and pathogenicity of porcine epidemic diarrhea virus - Sun, Yingshuo; Gong, Ting; Wu, Dongdong; Feng, Yongzhi; Gao, Qi; Xing, Jiabao; Zheng, Xiaoyu; Song, Zebu; Liu, Xing; Chen, Xiongnan; Sun, Yankuo; Zhang, Guihong; et al. (Frontiers in Microbiology, 2023)
Porcine epidemic diarrhea (PED) is an enterophilic infectious disease caused by the porcine epidemic diarrhea virus (PEDV), which can lead to dehydration-like diarrhea in piglets with a mortality rate of up to 100%, causing huge economic losses to the global pig industry. In this study, we isolated two PEDV strains, FS202201 and JY202201, from diarrheal samples collected from two new PED outbreak farms in 2022. The S gene and whole gene sequence phylogenetic analyses showed that both strains belong to the GⅡc subtype, a widely prevalent virulent strain. Compared with FS202201, JY202201 harbored substitution and deletion mutations in nsp1. The effects of the different mutations on viral pathogenicity were investigated using piglet challenge experiments. Both FS202201 and JY202201 infected piglets showed severe diarrhea and significant intestinal tissue lesions at an infection dose of 10 4 TCID50/mL, with a mortality rate of 50%; however, JY202201 required an additional day to reach mortality stabilization. An infection dose of 10 3 TCID50/mL reduced diarrhea and intestinal tissue lesions in piglets, with mortality rates of the two strains at 16.7% and 0%, respectively. In addition, PEDV was detected in the heart, liver, spleen, lungs, kidneys, mesenteric lymph nodes, stomach, large intestine, duodenum, jejunum, and ileum, with the highest levels in the intestinal tissues. In conclusion, this study enriches the epidemiology of PEDV and provides a theoretical basis for the study of its pathogenic mechanism and prevention through virus isolation, identification, and pathogenicity research on newly identified PED in the main transmission hub area of PEDV in China (Guangdong).